The Calcium Paradox – Calcium Dietary Intake and Supplementation in the Context of Calcium Oxalate Renal Calculus - Tanishka Koul; Bushra Shaida (International Journal of Sustainability, 2025)
Renal Calculi, also known commonly as kidney stone is one of the most common manifestations of kidney function dysregulation causing discomfort and alterations to an individual’s life. Although kidney stones come in a variety of forms, calcium oxalate stones are the most prevalent kind. These Calcium Oxalate renal stones often arise from various issues like metabolic imbalances, dehydration and dietary imbalances. About 70–80% of kidney stones are calcium oxalate stones, and the lifetime risk of developing kidney stones is 6–12% for the general population. Recent studies have brought forth a fact that contrary to common misconceptions or beliefs, reducing dietary calcium intake does not ensure prevention of calcium oxalate stones. On the other hand, calcium intake restriction may actually be dangerous since it can contribute to calcium deficiency and heighten the risk of other ailments in relation to it. This review highlights the paradox of calcium intake in relation to the formation of most common renal calculi – Calcium Oxalate stones. This paper basically highlights the balance needed between ensuring sufficient calcium intake for bone strength and reducing the risk of renal calculi formation. Achieving a balance is vital. Calcium is essential for building strong bones and supporting essential bodily functions, but an imbalance – specially caused due to its deficiency can be risky. So, it is important to understand the advantages of obtaining calcium from dietary sources, the dangers of calcium deficiency, and the various diagnostic methods to monitor calcium related health concerns
Keywords: Renal calculi; calcium deficiency; calcium intake; calcium oxalate stones; kidney stones; renal health